Training on the Creation of 3d Learning Media for Lithosphere Materials in the Geography Teachers' Working Group (Mgmp) of Senior High Schools in Padang City - Chandra, Deded; Edial, Helfia; U, Iswandi; Nova, Sari; Putri, Sri Kandi; Pertiwi, Mentari Dian (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This article aims to enhance teachers' skills in creating interactive learning media and to improve teachers' understanding of pedagogical aspects that can be seen in the lesson planning process, especially in the selection of models or methods and learning media. This activity was conducted at Building B, Room 23302, Faculty of Social Sciences, Universitas Negeri Padang, using training methods, question and answer sessions, and practical exercises. Participants in this activity included Geography subject teachers from senior high schools in Padang City. The activity included training on how to design effective learning media and also provided training on creating interactive learning media on the topic of Lithosphere for high school geography teachers in Padang City. The training, conducted together with the Geography subject teachers, resulted in the creation of three-dimensional learning media and improved the teachers' skills in creating three-dimensional Lithosphere learning media. Through this training, teachers experienced an improvement in their understanding of pedagogical aspects, especially in lesson planning (RPP), particularly in the selection of models and learning media. Geography teachers also gained a better understanding of the competencies required to design and use media effectively, enabling them to create quality, efficient, and interactive learning experiences.